Urban vs. marine based oil pollution in the Strait of Johor, Malaysia : a century record. - Sakari, Mahyar; Zakaria, Mohamad P.; Mohamed, Che A. Rahim; Lajis, Nordin H.; Chandru, Kuhan; Bahry, Pourya S.; Mokhtar, Mazlin B.; Shahbazi, Azadeh (Taylor & Francis, 2010)

(untitled)
Polycyclic aromatic hydrocarbons (PAHs) constitute a class of organic pollutants in the environment that come from combustion of organic matter and petroleum products and from natural sources. Reconstruction of PAH history from two sedimentary cores of the Strait of Johor in peninsular Malaysia showed predominance of urban over marine-based sources of oil pollution. Laboratory analysis of the cores found oil pollution from city-sourced material since 1910 and 1940 in the near-shore and offshore samples, respectively. Using hopane as molecular biomarker of petroleum pollution, this study found a predominance of Southeast Asian-originated oil and its derivatives. This study concludes that crankcase oil, asphalt, street dust and urban sediments considerably contribute to oil pollution of the study area.